Determination of students' physical and psychological abilities in learning basketball free throws - Suci Ramadani; Muhamad Sazeli Rifki (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Free-throw performance is a crucial skill in basketball, directly affecting scoring without defensive interference. This study systematically reviewed national and international literature (2018–2024) to examine physical, psychomotor, and psychological determinants of free-throw accuracy in youth players. Using a PRISMA-based approach and thematic synthesis, three core variables were analyzed: upper-limb explosive power, hand–eye coordination, and concentration. Findings indicate that upper-limb strength enhances elbow stability, release speed, and movement efficiency; hand–eye coordination improves visual-motor integration and shooting precision; and concentration supports motor control, emotional stability, and resistance to competitive pressure. These factors interact synergistically to enable consistent and accurate free throws. The review highlights the importance of integrated training programs combining physical conditioning, coordination drills, and mental skills practice for youth development. Results provide evidence-based guidance for coaches to design holistic interventions that optimize free-throw performance and contribute to long-term skill consistency in competitive basketball settings.